Influence of a training session on postural stability and foot loading patterns in soccer players - Vanessa K.N. Petry; Jürgen R.J. Paletta; Bilal F. El-Zayat; Turgay Efe; Nathalie S.D. Michel; Adrian Skwara (Orthopedic Reviews, 2016)
Sport specific movements coming along with characteristic plantar pressure distribution and a fatigue of muscles result in an increasing postural sway and therefore lead to a decrease in balance control. Although single soccer specific movements were expatiated with respect to these parameters, no information is available for a complete training session. The objective of the present observational study was to analyze the direct influence of soccer training on postural stability and gait patterns and whether or not these outcomes were altered by age. One hundred and eighteen experienced soccer players participated in the study and were divided into two groups. Group 1 contained 64 soccer players (age 13.31±0.66 years) and Group 2 contains 54 ones (age 16.74±0.73 years). Postural stability, static plantar pressure distribution and dynamic foot loading patterns were measured. Our results showed that the soccer training session, as well as the age, has relevant influence on postural stability, while the age only (excluding the training) has an influence on static plantar pressure distribution. The parameters of dynamic assessment seem therefore to be affected by age, training and a combination of both. Training and young age correlate with a decreased postural stability; they lead to a significant increase of peak pressure in the previously most loaded areas, and, after reaching a certain age and magnitude of absolute values, to a change in terminal stance and preswing phase of the roll-over. Moreover, younger players show an inhomogenous static plantar pressure distribution which might be the result of the decreased postural control in the young age.